2012
DOI: 10.4149/neo_2012_022
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of methylation changes in 9p21 region in patients with myelodysplastic syndromes and acute myeloid leukemia

Abstract: Epigenetic de novo methylation of CpG islands is an important event in malignant transformation. Two genes are frequently methylated: cyclin-dependent kinase inhibitor 2B (CDKN2B) and cyclin-dependent kinase inhibitor 2A (CDKN2A). In our study methylation of these genes was studied in 63 patients with myelodysplastic syndromes (MDS), 2 with myelodysplastic/myeloproliferative neoplasms (MDS/MPN) and 13 with acute myeloid leukemia (AML). Five patients were monitored during 5-azacytidine treatment. Twenty-six hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 27 publications
(35 reference statements)
0
20
0
Order By: Relevance
“…Mainly by deregulation of the cell cycle and the TGF-β pathway (Matsuno et al, 2005). Hypermethylation of p15 gene was reported in myelodysplastic syndrome (MDS), and may play role in progression of MDS to AML (Aggerholm et al, 2006;Hofmann et al, 2006;Cechova et al, 2012). Silencing of p16 gene by hypermethylation was shown to be mediated by a similar mechanism to p14 and TMS1 gene silencing (Esteller, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Mainly by deregulation of the cell cycle and the TGF-β pathway (Matsuno et al, 2005). Hypermethylation of p15 gene was reported in myelodysplastic syndrome (MDS), and may play role in progression of MDS to AML (Aggerholm et al, 2006;Hofmann et al, 2006;Cechova et al, 2012). Silencing of p16 gene by hypermethylation was shown to be mediated by a similar mechanism to p14 and TMS1 gene silencing (Esteller, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many hematologic neoplasias also acquire epigenetic changes, which may have a profound effect at the level of gene expression (Bonifer and Bowen, 2010;Jelinek et al, 2011). For example, the inactivation of tumor suppressor genes by promoter hypermethylation contributes to the initiation and progression of MDS and AML (Bies et al, 2010;Cechova et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Previous study has indicated aberrant DNA methylation associated with leukemogenesis [10]. As a typical epigenetic modifications, aberrant DNA methylation was observed in lymphoid/hematopoietic malignancies, including AML [4], [11], CML [12], [13], ALL [1], [14], and CLL [15], [16].…”
Section: Introductionmentioning
confidence: 99%